2010
DOI: 10.1111/j.1468-3083.2010.03609.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin disorders in chronic psychiatric illness

Abstract: Many chronic psychiatric patients have skin problems. Clinical examination of the skin is important to discover these problems. Patients with diabetes mellitus are particularly at risk for skin infections. Because of their relationship with overweight and diabetes mellitus, atypical antipsychotics may be partly responsible for these serious complications. Only a few other relationships between psychiatric medication and specific skin problems were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…This could especially be the case in long‐stay patients, because of the lower frequency of consultations we registered for this group of patients. In our study of the prevalence of skin disease among long‐stay patients unreported skin problems were found in 37% of the patients 8 . Furthermore, patients could also have been helped by nurses, the hospital chiropodist or psychiatrists who were all not involved in this survey.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…This could especially be the case in long‐stay patients, because of the lower frequency of consultations we registered for this group of patients. In our study of the prevalence of skin disease among long‐stay patients unreported skin problems were found in 37% of the patients 8 . Furthermore, patients could also have been helped by nurses, the hospital chiropodist or psychiatrists who were all not involved in this survey.…”
Section: Discussionmentioning
confidence: 83%
“…Because of the higher prevalence of diabetes mellitus among psychiatric patients this is an important finding, the more since diabetes can be induced by psychiatric medication 12 . In our recent study on the prevalence of skin disease in residential psychiatric patients, we found patients with diabetes mellitus to have a 10‐fold increased risk for skin infections 8 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…14,15 Diabetes mellitus and obesity can confound the association of bacterial skin infections and psychiatric morbidity as they are both associated with an increased frequency of infectious skin diseases and are also more frequently encountered in psychiatric patients, often as a result of side effects of psychiatric medications. 16 To our knowledge, no large-scale studies have examined the frequency and nature of psychiatric morbidity in patients with bacterial infections of the skin and subcutaneous tissue.…”
mentioning
confidence: 99%